Managing the diabetic foot - Edmonds, M. E.; Foster, Alethea V. M. (Chichester, West Sussex, UK : John Wiley & Sons Inc., 2014)
Foot problems in diabetic patients are some of the most challenging complications to treat, due to an often quite late presentation of symptoms from the patient. Therefore visual recognition of presenting clinical signs is absolutely key for a successful diagnosis and subsequently, the right management programme. The 3rd edition of Managing the Diabetic Foot once again provides a practical, handy and accessible pocket guide to the clinical management of patients with severe feet problems associated with diabetes, such as ulcers, infections and necrosis. By focusing on the need for a.
Managing stage 1 : the normal foot -- Managing stage 2 : the high-risk foot -- Managing stage 3 : the ulcerated foot -- Managing stage 4 : the infected foot -- Managing stage 5 : the necrotic foot -- Managing stage 6 : the unsalvageable foot.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Diabetes -- Complications; Diabetic Foot -- therapy; Diabetes -- Complications; Diabetes mellitus; Diabetic foot -- Therapy; Medicine; Electronic books